2021
DOI: 10.21203/rs.3.pex-1495/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of powerball versus mulligan mobilization with movement on pain and function in patients with lateral epicondylitis: a randomised control trial

Abstract: Background: Lateral epicondylitis (LE), most commonly referred to as Lateral Elbow Tendinopathy (LET) or Tennis Elbow is one of the commonest repetitive stress syndromes seen in elbow joint. Tendinopathy, an injury to forearm extensor muscles. These muscles arise from the distal end of humerus from lateral epicondylar region. In many cases, involvement of extensor carpi radialis brevis muscle’s insertion is seen. This study focuses on the treatment of a person with LE which occurs in repeated upper extremity m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These findings are consistent with previous research. Lucado et al (2019) demonstrated that MWM significantly improved VAS pain ratings and grip strength in patients with lateral elbow tendinopathy (10)(11)(12)(13)(14). Similarly, Basak et al (2018) found that both wrist manipulation and progressive exercises significantly improved elbow pain and grip strength, with combined treatments showing even greater improvements (11).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings are consistent with previous research. Lucado et al (2019) demonstrated that MWM significantly improved VAS pain ratings and grip strength in patients with lateral elbow tendinopathy (10)(11)(12)(13)(14). Similarly, Basak et al (2018) found that both wrist manipulation and progressive exercises significantly improved elbow pain and grip strength, with combined treatments showing even greater improvements (11).…”
Section: Discussionmentioning
confidence: 98%
“…In conclusion, while both treatment modalities are beneficial, MWM appears to be more effective in reducing pain and improving functional disability, whereas Progressive Strengthening Exercises excel in enhancing grip strength (14)(15). This study underscores the importance of tailored treatment approaches based on individual patient needs and highlights the potential for combining these modalities to optimize clinical outcomes in patients with lateral epicondylitis.…”
Section: Introductionmentioning
confidence: 99%